2018
DOI: 10.18632/oncotarget.25453
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node density in papillary thyroid carcinoma is a prognostic factor after adjusting for pathological stage

Abstract: We investigated the possible association between the lymph node density and survival outcomes in differentiated papillary thyroid carcinoma, and examined whether the lymph node density was a predictor in a multivariate analysis adjusted for the pathological stage in the eighth edition of the Union for International Cancer Control Tumor-Node Metastasis Classification of Malignant Tumors. A total of 543 patients with papillary thyroid carcinoma were enrolled. We performed restaging according to the eighth editio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Our present findings, which showed a significant association between high FDG-uptake parameters and shorter OS, are consistent with those in previous studies (8,(13)(14)(15). Pathological stage by restaging based on using the eighth edition of the staging manual AJCC and UICC8 has been showed to be a useful predictor in several types of cancer (3,6,7). In 4,520 patients with salivary gland cancer from the National Cancer Database in United States of America, restaging stage such as pN3b was significantly associated with survival outcomes (6).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our present findings, which showed a significant association between high FDG-uptake parameters and shorter OS, are consistent with those in previous studies (8,(13)(14)(15). Pathological stage by restaging based on using the eighth edition of the staging manual AJCC and UICC8 has been showed to be a useful predictor in several types of cancer (3,6,7). In 4,520 patients with salivary gland cancer from the National Cancer Database in United States of America, restaging stage such as pN3b was significantly associated with survival outcomes (6).…”
Section: Discussionsupporting
confidence: 93%
“…In 4,520 patients with salivary gland cancer from the National Cancer Database in United States of America, restaging stage such as pN3b was significantly associated with survival outcomes (6). We also showed that the pathological stage by restaging was significantly associated with OS in 543 patients with papillary thyroid cancer (7). Recently, we showed the significant association between 18 F-FDG-uptake parameters of primary tumor and OS in 28 patients with oral cancer by multivariate analysis adjusting for UICC8 pathological stage (3).…”
Section: Discussionmentioning
confidence: 55%
“…28 Suzuki et al reported that LNR of LLNs ≥0.3 were significantly associated with poorer overall and disease-specific survival. 29 Schneider et al also found LNR ≥0.42 was a strong determinant of shorter disease-specific survival. 30 Previous studies have investigated the prognostic impact of LNR of CLNs alone or CLNs and LLNs together.…”
Section: Discussionmentioning
confidence: 94%
“…Gao et al compared the prognostic value of number and LNR of metastatic lymph nodes on clinical response in PTC and pointed out that LNR seemed to negatively predict excellent response better than the number of metastatic lymph nodes in PTC patients with ≤10 dissected lymph nodes, whereas the opposite trend was observed in those with >10 dissected lymph nodes 28 . Suzuki et al reported that LNR of LLNs ≥0.3 were significantly associated with poorer overall and disease‐specific survival 29 . Schneider et al also found LNR ≥0.42 was a strong determinant of shorter disease‐specific survival 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Generally, there is no good reason to suppose that there is an underlying dichotomy. 16 In spite of this, most cancer-specific survival studies employed dichotomization, producing metastatic lymph node ratio cutpoints which varied from 0.19 for MTC 14 to 0.3 for both papillary thyroid cancer 17 and poorly differentiated thyroid cancer. 18 However, findings deriving from papillary thyroid cancer and poorly differentiated thyroid cancer, originating from follicular thyroid cells that synthesize thyroid hormones, cannot be generalized to MTC, a neuroendocrine malignancy originating from parafollicular C cells that synthesize calcitonin.…”
Section: Discussionmentioning
confidence: 99%